정면충돌에서 노인운전자의 중증도에 영향을 주는 요인 분석 - 전혁진(Hyeok-Jin Jeon) (한국화재소방학회 논문지, 2019)
The increase in the elderly population also increased the damage and deaths of the elderly drivers. However, studies on the severity and severity of the elderly driver are not actively conducted and the factors are unknown. In this study, I tried to find out the factors affecting the damage and severity of the elderly driver in the frontal collision and to utilize them additionally in the severity classification. Collision Deformation Classification (CDC) Code was used to check the extent of damage to the vehicle. Abbreviated Injury Scale (AIS) was used to determine the injury parts and severity of injury, and the Injury Severity Score (ISS) to confirm the severity of the patient. The odds ratios of severe injury patients were found to be 7.381 in the subjects with 5 or more deformation extent and the ${β}$ value of the deformation extent was 0.453 in the analysis of the severity by linear regression analysis. Therefore, the degree of deformation extent of 5 or more can be suggested as a criterion that can be used additionally to the severity classification in the elderly driver. 노인인구의 증가로 노인운전자의 손상과 사망자도 증가하였다. 하지만 노인운전자의 손상과 중증도에 대한 연구는 활발히 이루어지지 않아 영향 요인을 파악하지 못하고 있다. 본 연구에서는 정면충돌에서의 노인운전자에 손상과 중증도에 영향을 미치는 요인을 찾아 중증도 분류에 추가적으로 활용하고자 하였다. Collision Deformation Classification Code를 통해 차량 파손 정도를 확인하였으며 간편손상척도(Abbreviated Injury Scale, AIS)로 손상부위와 정도를, 손상중증도점수(Injury Severity Score, ISS)로 환자의 중증도를 확인하였다. 중증외상환자의 발생률은 5이상의 차량 파손 정도를 가진 대상자에서 Odds ratio가 7.381로 나타났으며 선형회귀분석을 통한 중증도 요인 분석에서도 차량 파손 정도의 ${β}$값이 0.453으로 나타났다. 따라서 5이상의 차량 파손 정도는 노인운전자에서 중증도 분류에 추가적으로 활용될 수 있는 기준으로 제안될 수 있다.